Force-velocity relationship between sprinting and jumping testing procedures - Stavridis, I.; Tsopanidou, A.; Tsolakis, C.; Zacharogiannis, E.; Koulouvaris, P.; Paradisis, G. (ISBS Proceedings Archive (Michigan), 2020)
The aim of this study was to examine the relationship between the mechanical characteristics of the horizontal and vertical Force-velocity (F-v) profile as well as the performance variables of the sprinting and jumping testing procedures. Twenty high-level sprinters performed two maximal sprints and squat jumps against multiple external loads. Our main findings revealed very large correlations for maximal mechanical power output (Pmax) (r=0.72), as well as for performance variables between the sprinting and jumping tasks (r=-0.81) and large correlations for maximal velocity (V0) (r=0.66). The maximal force (F0) and the slope of the F-v relationship (F-v slope) were not significantly correlated between both tasks. These results suggest that both testing procedures should be performed in order to gain a deeper insight into the maximal mechanical properties and function of the lower-body muscles in high-level sprinters.